The Alignment of Solution-Focused Brief Counseling in Helping to Achieve Resilience - Hendriani, Wiwin; Mulawarman, Mulawarman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2020)
This review of the literature aims to explain why Solution-Focused Brief Counseling (SFBC) is appropriate as an approach in helping individuals achieve resilience, after experiencing certain traumatic events. This study was motivated by the need for a conceptual explanation of what approaches can be recommended so that recovery of post-traumatic psychological conditions and the achievement of resilience can be carried out with more efficient and effective processes. The method used in this study was comparative analysis, involving a variety of relevant literature to identify alignment concepts between SFBC and resilience. The intended literature includes reference books, reputable scientific journal articles, and various information from credible sources. The results of the study show that there are points of similarity in the two theories, both in terms of basic assumptions and concepts related to the intervention process which confirms the relevance and accuracy of the use of SFBC in helping individuals achieve post-traumatic resilience. This study can then be used as a scientific foothold for the application of SFBC in an effort to increase individual resilience in various contexts.